UPAYA MENINGKATKAN KEMAMPUAN SISWA UNTUK MENGUNGKAKAN MAKNA DALAM MONOLOG PENDEK BERBENTUK PROCEDURE MELALUI METODE DEMONSTRASI DI KELAS VII A MTS WALISONGO ULUJAMI - M. Fajru Sidiq (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2010)
nglish Learning – Teaching must made the active students. It hopes his or her creative in stating meaning in material was given. Procedure text in based is material can be expressed creatively. The moment was happened blowing on the text. This expression absolutely based on the capability of teacher in growing up the confidential in students. Beside, the right - method in teaching has influence in learning English. The Method offered in this research is demonstrative method. This made students observing the situation and moment in related to the text. They could get close with learning directly. Then, the result of study is the ability of students in stating meaning on text.